Retailers' responsibility towards consumers and key drivers of their development in Poland - Grażyna Śmigielska; Renata Oczkowska (Administrative Sciences, 2017)
Multinational retailers are now very powerful and their activities could influence whole economies. In this paper, we investigate why they engage in corporate social responsibility (CSR) practices towards consumers, how it fosters sustainable development, and what the role of institutions are in the process of developing CSR strategies. Changes that have taken place in Poland since 1989, when the transition process into a market economy started, constituted an excellent research field due to the fact that the retail market was not saturated at the beginning, consumers were only slightly protected by the law, and there were no institutions promoting the implementation of social responsibility standards by companies. Research involving analysis of secondary data drawn from retailers' websites, CSR reports, and published data relating to the CSR institutions allowed the following: (1) identification of three stages of development in consumers' conception of CSR characterized by the immoral, amoral, and moral management; (2) showing that these activities have a business case; and (3) explaining the role of institutions and competition in this process. It is also shown how multinational retailers could contribute to the sustainable development of less mature markets in which they invest.
Keywords: 350; corporate social responsibility; consumers; multinational retailers; institutions; sustainable development; Poland